Press and Social Representations of Indigenous Communities in the Colombian Media - Merchán Cante, Harvey Humberto (Cuadernos de Lingüística Hispánica, 2023)
This article uses the methodological perspective of Jean-Blaise Grize and Teun van Dijk’s macrostructures to analyze the Colombian media’s arguments about indigenous communities. Furthermore, it presents advances in the discursive configuration of these media and their relevant role in the construction of social representations of violence and indigenous groups in Colombia.Otherwise, it is taken into account that the way in which the media present news about violence can promote discrimination against these indigenous peoples;therefore, it could be argued that the naturalization of violence against indigenous peoples in the media is a strategy used to perpetuate certain social and ideological positions.